Mechanisms in two-story X-braced frames - Shen, Jay; Wen, Rou; Akbaş, Bülent (Elsevier Sci Ltd, 2015)
This paper presents a study to reveal actual mechanisms and seismic loading patterns on the braced-intersected beams in two-story X-braced frames (X-braced frames) and discusses the impacts of yielding beams on critical components, such as braces and connections. First, the seismic response of various X-braced frames with different heights and design assumptions is presented to observe actual mechanisms and seismic load patterns on weak and strong beams during earthquake ground motions. Then the simulations with finite element method are presented to help understand the mechanisms observed in the seismic response of the X-braced frames. The paper concludes that (1) the first-mode mechanism in multi-story concentrically braced frames, anticipated by AISC 341, is a rare occasion and leads to light sections for brace-intersected beams in X-braced frames that most likely undergo significant inelastic deformation; (2) yielding of the brace-intersected beam alters the mechanism in many ways, which, in turn, further increases inelastic deformation in the beam; (3) vertical inelastic displacement at beam middle span causes significantly additional ductility demand on braces, gusset plates, and beam-to-column connections that are not considered in current design practice; and (4) inelastic deformation of brace-intersected beams results in the redistribution of the total input energy demand among the components of the X-braced frame, adversely increasing the demand on fracture-prone components such as braces and gusset plates. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Actual mechanism; Brace-intersected beams; Two-story X-braced frames